Transcriptome Analysis Reveals the Senescence Process Controlling the Flower Opening and Closure Rhythm in the Waterlilies (Nymphaea L.) - Li, Zhaoji; Zhou, Weijuan; Wang, Peng; Chen, Yanfu; Huo, Shaojie; Wang, Jian; Tian, Daike; Niu, Jun; Zhao, Ying; Song, Xiqiang (Frontiers in Plant Science, 2021)
Most waterlily flowers open at dawn and close at dusk usually for three to four days, and thereafter wilt in few days. The short lifespan of flowers restricts the development of the flower postharvest industry. The termination of flower movements is a key event during flower ageing process. However, it is still unclear when the senescence process initiates and how it terminates the movement rhythm. In this study, we observed that the opening diameter of flowers was the smallest on the fourth (last) flowering day. Subsequent transcriptome profiles generated from petals at different flowering stages showed that the multiple signaling pathways were activated at the last closure stage (Time 3, T3) of the flowers , including Ca2+, reactive oxygen species (ROS) and far red light signaling pathways, as well as auxin, ethylene and jasmonic acid signaling pathways. Moreover, In terms of cell metabolism regulation, the genes related to hydrolase (protease, phospholipase, nuclease) were upregulated at T3 stage, indicating that petals entered the senescence stage at that time; and the genes related to water transport and cell wall modification were also differentially regulated at T3 stage, which would affect the ability of cell expand and contract, and eventually lead to petal not open after the fourth day. Collectively, our data provided a new insight into the termination of flower opening in the waterlilies, and a global understanding of the senescence process of those opening-closure rhythm flowers.